Programmable Negative Differential Resistance Effects Based on Self-Assembled AuPPy Core-Shell Nanoparticle Arrays - Zheng, Jianzhong (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.